A Price Paid for Our Internal Strife: Escalated Intragroup Aggression and the Evolution of Ingroup Derogation - Wu, Qi; Liu, Wang; Li, Chen; Li, Xiongfeng; Zhou, Ping (Frontiers in Psychology, 2016)
From evolutionary reasoning, we derived a novel hypothesis that ingroup derogation is an adaptation to a special ecological condition in which the greater threat of aggression is incurred by ingroup members. This hypothesis was tested and supported across five studies. Specifically, the computational modeling found that ingroup derogation could easily evolve if the chance of death incurred by intragroup conflicts was no less than 10%. Further behavioral experiments on Chinese participants showed that the ingroup derogation mechanism responded to heuristic social category cues and it responded more strongly when participants subjectively felt more vulnerable to interpersonal aggression, or when there were contextual cues of aggression in the immediate environment. Additional results showed that Chinese participants responded more strongly to aggression cues originating from ingroup members and that they endorsed more ingroup derogation attitudes even when the ingroup and outgroup members were both displaying cues of aggression. In addition, the results also revealed that the Chinese participants perceived more intentions of aggression from ingroup members than from outgroup members even in the absence of any clear signs of those intentions, and such a bias was positively correlated with ingroup derogation attitudes. Taken together, these results suggest that ingroup derogation is related to the evolved response of intragroup aggression management system.